Primary Cutaneous Nocardiosis in an Adolescent with Crohn Disease - Steven A. Svoboda; Joshua D. Eikenberg (Hindawi Limited, 2020)
Nocardia is an aerobic, Gram-positive, partially acid-fast bacterium that often manifests as pulmonary infection since the primary route of entry is via the respiratory tract. As an opportunistic organism, Nocardia primarily affects immunocompromised individuals. Infection with Nocardia is uncommon. Primary cutaneous nocardiosis which is caused by percutaneous inoculation is even more rare. Here, we report a case of primary cutaneous nocardiosis in an adolescent with Crohn disease receiving treatment with adalimumab and azathioprine. Early identification and treatment are important to prevent disease progression and to avoid severe complications. Diagnosis is made principally by culture. Given that culture results may take up to two weeks to return, primary cutaneous nocardiosis should be maintained in the differential for any superficial cutaneous infection that arises in individuals undergoing treatment with immunosuppressive agents.